PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI PERIODE 2016–2023 - Saleh, Rahmat; Iman Firmansyah; Asty Khairi Inayah Syahwani; Lesia Fatma Ginoga (Jurnal Bisnis Terapan, 2026)
This study aims to examine the effect of fundamental factors on stock prices of property companies listed on the Indonesia Stock Exchange (IDX) during the 2016–2023 period. The independent variables are Return on Equity (ROE), Debt to Equity Ratio (DER), Earnings Per Share (EPS), Current Ratio (CR), and Accounts Receivable Turnover (ART), while the dependent variable is stock price measured by the closing stock price. This study employs a quantitative approach with an explanatory research design. The population consists of 35 property companies listed on the IDX during 2016–2023. Using purposive sampling, 30 companies that met the research criteria were selected, resulting in 240 observations. Secondary data were obtained from the Indonesia Stock Exchange (IDX) and the Indonesian Capital Market Directory (ICMD). Data were analyzed using multiple linear regression. The results indicate that ROE, DER, EPS, CR, and ART simultaneously affect stock prices. Partially, ROE, DER, and EPS have a positive and significant effect on stock prices, whereas CR and ART do not have a significant effect. The adjusted coefficient of determination shows that the model explains 22.7% of stock price variation. These findings indicate that investors place greater emphasis on profitability and earnings performance than on liquidity and activity ratios when evaluating property companies.